2016
DOI: 10.1177/0009922816632346
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Children With Gay Fathers

Abstract: An online survey was distributed via snowball sampling and resulted in responses from 61 gay fathers raising children in 2 states. Fathers reported on the barriers they experienced and the pathways they took to becoming parents. They reported also on experiences of stigma directed at them and their children, especially from family members, friends, and people in religious institutions. Despite these difficulties they reported that they engaged actively in parenting activities and that their child(ren)'s well-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Further, gay fathers had faced unique challenges in making their adoptive and unconventional family as they anticipated and prepared themselves and their children for the discrimination they may encounter when revealing their family configuration. In this regard, a study of US gay fathers reported that in contrast with those living in California, most of the gay fathers who lived in Tennessee reported higher levels of parenthood-related stigma and tended to avoid situations in which they might encounter this stigma (Perrin et al, 2016 ) revealed.…”
Section: Resultsmentioning
confidence: 99%
“…Further, gay fathers had faced unique challenges in making their adoptive and unconventional family as they anticipated and prepared themselves and their children for the discrimination they may encounter when revealing their family configuration. In this regard, a study of US gay fathers reported that in contrast with those living in California, most of the gay fathers who lived in Tennessee reported higher levels of parenthood-related stigma and tended to avoid situations in which they might encounter this stigma (Perrin et al, 2016 ) revealed.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, gay men report suspicion and criticism for their decision to be parents from gay friends who have not chosen parenthood, barriers in the adoption process, and isolation in their parental role. 14,15 Gay men who became parents while in a heterosexual relationship may face difficulties maintaining custody or obtaining legal parenting rights for a new spouse. 14 Adoption and surrogacy options are also limited by their high cost.…”
mentioning
confidence: 99%
“…Five of the 22 papers were normative comparative studies and, therefore also included heterosexual persons (Crawshaw & Montuschi, 2014;Goldberg & Smith, 2008a;Goldberg & Smith, 2014;Lavner et al, 2014). Nine of the studies focused on female samples (Chabot & Ames, 2004;DeMino et al, 2007;Dunne, 2000;Goldberg, 2006a;Goldberg, 2006b;Goldberg & Smith, 2008b;Manley et al, 2018;Ross et al, 2005), six on male samples (Brinamen & Mitchell, 2008;Gianino, 2008;Goldberg et al, 2012;Perrin et al, 2016;Tornello & Patterson, 2015;Wells, 2011); one of them also included transgender persons (Klittmark et al, 2019); and the remainder included males and females (Brown et al, 2009;Crawshaw, & Montuschi, 2014;Goldberg & Smith, 2011;Lavner et al, 2014). Considering a total of 2081 participants, across the 22 papers, 834 persons defined themselves as lesbian women, 1197 as gay men, 30 as bisexual individuals, and 20 as plurisexual, queer, or pansexual.…”
Section: Coding Of Studiesmentioning
confidence: 99%
“…Both gay and lesbian parents reported support from their families of origin (Brinamen & Mitchell, 2008;Brown et al, 2009;DeMino et al, 2007;Dunne, 2000;Gianino, 2008;Goldberg, 2006;Goldberg & Smith, 2011;Perrin et al, 2016;Ross et al 2005;Wells, 2011). This type of support increased across the transition to parenthood (Brinamen & Mitchell, 2008;Brown et al, 2009;Goldberg, 2006;Goldberg & Smith, 2011), even when the family of origin was not initially supportive of the decision to have children (Brown et al, 2009;Ross et al, 2005) or at the moment of coming-out (Gianino, 2008;Wells, 2011).…”
Section: Families Of Originmentioning
confidence: 99%
See 1 more Smart Citation